ANALISIS EKSTRAKURIKULER PRAMUKA DALAM PEMBENTUKAN KARAKTER DISIPLIN SISWA SEKOLAH DASAR - Nurlaila; Anggit Merliana; Riefki Fiestawa (STKIP Subang, 2026)
Scouting extracurricular activities are additional activities conducted outside regular class hours and are mandatory in every school. Their purpose is to help students develop good disciplinary character. The importance of strengthening disciplinary character values is based on the fact that many deviant behaviors contrary to disciplinary norms are currently occurring, such as arriving late to school, not wearing uniforms according to school regulations, and not completing assignments on time. Therefore, this study aims to determine the role of scouting activities in shaping the disciplinary character of elementary school students. This research uses a qualitative approach with a descriptive method, and data were collected through a literature study. The results of the study indicate that scouting extracurricular activities have a positive impact on the development of students’ disciplinary character. This is because scouting activities are considered interesting, making it easier for students to be trained and habituated to discipline through these activities. Thus, it can be concluded that scouting extracurricular activities play an important role in shaping the disciplinary character of elementary school students.